Effects of Mirtazapine on the Sleep Wake Rhythm of Geriatric Patients with Major Depression: An Exploratory Study with Actigraphy - Rothschild-Fuentes, B.; Roche, A.; Jiménez-Genchi, A.; Sánchez-Ferrer, J. C.; Fresan, A.; Muñoz-Delgado, J. (Pharmacopsychiatry, 2013)
Major depression and insomnia are among the most frequent neuropsychiatric syndromes in the geriatric population. Although most SSRI antidepressants affect sleep continuity, mirtazapine has been found to improve sleep continuity in patients with depression. The aim of the present study was to assess by actigraphic recordings changes in sleep patterns of geriatric patients with major depression before and during treatment with mirtazapine (30 mg).Patients aged 60 years or more with major depressive disorder were recruited at the outpatient service of a specialized mental health centre. Severity of depression was rated with the Montgomery-Asberg depression rating scale and subjective perception of sleep was assessed with the Pittsburgh sleep quality index (PSQI). Actigraphic parameters were registered 4 days before the onset of mirtazapine treatment (patients were drug free in this period of time) and recorded at day 60 of treatment with mirtazapine.A significant decrease was observed in the sleep fragmentation index. While a significant improvement was observed in the subjective assessment of quality after treatment with mirtazapine, actigraphic measures of sleep parameters did not show changes in line with mirtazapine treatment.Mirtazapine produces minimal changes on actigraphic measures in the sleep of elderly outpatients. Sleep produced by mirtazapine indicates a more pronounced effect in ≥ 80-year-old patients. This differential response should be considered during treatment of this clinical population.
Keywords: sleep disturbances; sleep deprivation; depression; depression treatment